When Unsuspected Crystallinity Ruins Biological Testing in Early Discovery: A Case Study - Claudi de Rocafiguera; Blanca Belsa; Mercè Font-Bardia; Cristina Puigjaner; Eduard Serra; Ana M. Cuartero-Albesa; Raimon Puig de la Bellacasa; José I. Borrell (MDPI AG, 2024)
The impact of the crystalline or amorphous structure of a solid on the solubility and pharmacokinetic properties of a drug candidate is always considered by the pharmaceutical industry during the development of a new drug; however, it is not so frequently considered during the early drug discovery process by organic and medicinal chemists, particularly those working in academia. We want to share, as an example, the false negative obtained in the biological testing of a solid sample of a tyrosine kinase inhibitor due to its unexpected crystallinity and lower solubility with respect to a solid amorphous batch of the same compound and the experimentation carried out to establish the origin of such a discrepancy.